LINK methodology training workshop with Heifer lead staff in Asia and Africa - International Center for Tropical Agriculture; Even, Brice; Gutiérrez, Ernesto (2016)
Participants of the LINK methodology training workshop held in Siem Reap talk about the 5-day experience. They present themselves and talk about the workshop held in which they learned about Heifer’s previous experience using LINK in Latin America and studied the LINK Methodology tools applying them to four selected value chains. The workshop included a field trip where trainees had to apply specific tools of the LINK methodology in two real cases. Participants also spent time planning the learning cycle’s next steps, preparing a work plan, a timeline and the backstopping plan. Videos include an introduction to the workshop, a video on lessons learned, and a video on the expectations of participants. Producción: Brice Even Edición: Ernesto Gutiérrez